Development of a management tool to prevent emotional burnout in project teams - M. M. Vasin; I. A. Elistratov; A. S. Kumkin (Вестник университета)
The article studies the phenomenon of emotional burnout in the framework of project team management. The authors of the article have considered the concept of emotional burnout, identified the causes of stress among project team members during project implementation and concluded that probability of emotional burnout syndrome can be reduced due to effective selection of project team by manager and balanced distribution of responsibilities among team members. As a solution for project managers, the authors have considered a “functional map” tool. A comparison of the functional map and a job description has been made in order to visualize distinctive features of the functional map. Based on the tool’s advantages and disadvantages analysis, the authors have proposed innovations to minimize probability of burnout syndrome among project team members. In conclusion, the authors have given their recommendations to project managers on controlling emotional burnout in project teams.